(3GdeSFhdjI GdJCOjHjI ddbVGI h CYVGA GdfjGHI GdYGeI aj GdJTQjY GdadSWjfj (B: s (3OQGSI ebGQfI (B/ s - (3CfhQ MeOGf GdTGYQs; (3UHQj eMeO GdSfhSjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3JfGhdJ aj gPg GdOQGSI ehVhY GdeSFhdjI GdJCOjHjI ddbVGI hCYVGA GdfjGHI GdYGeI aj GdbGfhf GdadSWjfj eY JHjGf CgejI OQGSI gPG GdehVhY deG ddbVGA ef CgejI aj ebjGS GdTYhH aj JbOegG hQbqjgG(B: (3hHOCfG GdOQGSI HJMOjO eGgjI GdfXGe GdbVGFj GdadSWjfj hGdhGbY GdJGQjNj hGdbGfhfj GdPj CqSS dHfI gGeI aj GdfXGe GdbVGFj GdadSWjfj(B: (3cPdc JfGhdfG bhGYO GdYed GdhXjaj GdbVGFj hHjGf eGgjI GdeNGdaI GdJCOjHjI ddbVGI hCYVGA GdfjGHI GdYGeI(B: (3hHjGf CQcGfgG heUGOQ JLQjegG hUhdkG Edi WHjYI GdhGLHGJ GdhXjajI GdedbGI Ydi YGJbge(B: (3hGNJJefG GdOQGSI HHjGf GdbhGYO GdELQGFjI dJCOjH GdbVGI hCYVGA GdfjGHI GdYGeI ef NdGd JfGhd ehVhY GdOYhi GdJCOjHjI hGdBdjGJ GdeJHYI aj eHGTQJgG hcjajI GdEMGdI hELQGAGJ GdJMbjb hUhdkG Edi JhbjY GdYbhHI GdJCOjHjI hGdeHGOF GdJj Jbhe YdjgG s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2015s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B445-458s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdJTQjY GdadSWjfjs; (3GdbVGI h CYVGA GdfjGHI GdYGeIs; (3GdeSFhdjI GdJCOjHjI s; (3VhGHW GdeSFhdjI GdJCOjHjI s; (3GdeNGdaI GdJCOjHjI s; (3hGLH GdMjGO s; (3hGLHGJ GdbGVj hYVh GdfjGHI s; (3GdeMGceI GdJCOjHjI s; (3ehGfY GdeSFhdjI GdJCOjHjI s; (3YhGQV GdeSFhdjI GdJCOjHjI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes